Expanding the University Music Ensemble: Lessons from an Intercultural Collaboration - Pearse, D. (Intersections, 2019)
Universities are increasingly aware of the need to re-envision curricula in order to engage with Indigenous perspectives, knowledge, and pedagogical approaches. University music programs, focused on the delivery of Western art music curricula, often struggle to implement meaningful engagement with Indigenous knowledge that goes beyond gestures. What practical steps can educators take to crack the seemingly impervious fabric of settler-colonial art music performance education? I draw on experiences from within an intercultural artistic collaboration of Indigenous and non-Indigenous artists and scholars in order to articulate pedagogical strategies applicable to university music performance ensemble classes.